(Re)discovering interpersonal relationships and self-authorship in STEM Graduate school through mindfulness. - Lausch, Sarah; Rossetto, Kelly (Journal of Social & Personal Relationships, 2023)
In this study, we utilized self-authorship theory to investigate how mindfulness practices support the connection between identity development and interpersonal relationships in STEM graduate students. In an 8-week self-led mindfulness intervention, 10 women from computer science and engineering graduate programs completed a variety of mindfulness exercises, including meditation, yoga, drawing and mindful daily activities (e.g., mindful dishwashing). We utilized a qualitative approach to gather an in-depth picture of each participant's individual progress. Data analysis showed that students' experiences, including supportive relationships and sense of identity in STEM, were influenced by interpersonal (dis)connections in and beyond academia. Mindfulness offered space and tools for students to reflect on their relationships and STEM identity and, if needed, modify them. Three themes are discussed: academic relationships with peers and advisors, including negotiating social comparisons; personal relationships with family and friends, including academia-life balance; and the relationship to their STEM identity.